A method for preparing laser cladding composite coating of nitriding die steel

CN118726968BActive Publication Date: 2025-02-25INST OF MECHANICS CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410799056.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-02-25
Estimated Expiration
2044-06-20

Smart Images

  • Figure CN118726968B_ABST
    Figure CN118726968B_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a laser cladding composite coating of a nitriding die steel, which comprises first selecting Ti alloy powder and H13 steel alloy powder for uniform powder mixing to obtain Ti-containing H13 steel powder, wherein the Ti alloy powder belongs to a micron-grade powder; at the same time, selecting Stellite alloy powder and H13 steel mixed powder for uniform powder mixing to obtain Stellite alloy-containing H13 steel powder; then respectively performing powder baking treatment on the Ti-containing H13 steel powder and the Stellite alloy-containing H13 steel powder; then cladding the Ti-containing H13 steel powder after powder baking treatment on the surface of the nitriding steel as a base layer, and then continuing to clad the Stellite alloy-containing H13 steel powder on the base layer as a working layer, so as to finally obtain a composite coating containing a base layer and a working layer. The invention has a reasonable concept and a simple process, and a composite coating is laser clad on the surface of the nitriding steel, and a cladding layer with no obvious holes and crack defects on the interface and excellent performance can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical fields of mold repair, laser additive manufacturing, laser cladding and the like, and in particular to a method for preparing a laser cladding composite coating of nitriding mold steel. Background Art

[0002] Before mold steel is put into actual use, a large number of surface nitriding processes are used. The main nitriding processes include gas nitriding, ion nitriding and liquid nitriding. Since a large amount of nitrides and tempered martensite are formed in the material structure after surface nitriding, the service life of mold steel will be greatly improved compared with before nitriding. Usually, the manufacturing cost of molds is high, and the use of surface nitriding process also has problems such as high energy consumption and long cycle. However, most mold damage occurs on the surface of parts. Using certain means to repair the damaged surface can effectively extend the service life of the mold, thereby reducing industrial production costs and improving economic and social benefits.

[0003] As a relatively mature remanufacturing technology, laser cladding technology has generated huge economic benefits in repairing high value-added parts. Different from non-nitrided parts, the preparation of high-quality repair coatings on the surface of nitrided die steel has the following difficulties:

[0004] (1) The solubility of nitrogen in molten steel is extremely low under normal pressure. Nitrogen easily forms nitrogen gas in the molten pool, which leads to denitrification of the material and the formation of a large number of nitrogen pores, that is, hole defects are easily generated at the interface between the cladding layer and the base material;

[0005] (2) The laser cladding process window for nitrided materials is narrower, and slight adjustments in process parameters may result in significant differences in material microstructure and performance;

[0006] Some literature points out (Vedani M, Previtali B, Vimercati GM, et al. Problems in laser repair-welding a surface-treated tool steel [J]. Surface & Coatings Technology, 2007, 201 (8): 4518-4525) that laser remelting is used to treat the nitrided layer so that the nitrogen in the molten metal escapes in the form of nitrogen gas before laser repair welding, which can effectively reduce the hole defects in the weld (its essence is to reduce the nitrogen content in the nitrided layer). However, there are a large number of brittle structures in the heat affected zone formed by laser remelting, which are prone to cracks during welding.

[0007] It can be seen that when laser repairing the surface of nitriding die steel, solving the formation of nitrogen pores in the cladding layer is the key to preparing a high-quality cladding layer. Material-organization-structure-performance integrated additive manufacturing technology is one of the mainstream directions of additive manufacturing technology. When laser repairing nitriding die steel, special design of cladding materials and cladding layers is required. When designing or selecting cladding materials for nitriding steel, in addition to the traditional cladding technology requirements that the lattice matching degree of the cladding material and the base material should be as high as possible, and the thermal expansion coefficient and melting point should be as close as possible, the nitrogen precipitation and release problems that occur in the nitriding layer after laser irradiation melting should also be considered.

[0008] To sum up, it is necessary to make further innovations on existing technologies. Summary of the invention

[0009] In view of the technical problems existing in the above-mentioned background technology, the present invention proposes a method for preparing a laser cladding composite coating of nitriding die steel. The method has a reasonable concept and a simple process. By preparing the laser composite coating on the surface of nitriding steel, a cladding layer with no obvious holes and crack defects on the interface and excellent performance can be obtained.

[0010] In order to solve the above technical problems, the present invention provides a method for preparing a laser cladding composite coating of a nitriding die steel, which comprises selecting Ti alloy powder and H13 steel alloy powder for uniform powder mixing to obtain Ti-containing H13 steel powder, wherein the Ti alloy powder is a micron-level powder; at the same time, selecting Stellite alloy powder and H13 steel mixed powder for uniform powder mixing to obtain Stellite alloy-containing H13 steel powder; then respectively performing powder baking treatment on the Ti-containing H13 steel powder and the Stellite alloy-containing H13 steel powder; then cladding the Ti-containing H13 steel powder after powder baking on the surface layer of the nitriding steel as a base layer, and then continuing to clad the Stellite alloy-containing H13 steel powder on the base layer as a working layer, so as to finally obtain a composite coating containing a base layer and a working layer.

[0011] The method for preparing the laser cladding composite coating of the nitriding die steel mainly comprises the following steps:

[0012] (1) Material selection

[0013] Select micron-sized Ti alloy powder and H13 steel alloy powder as raw materials for preparing the base layer, and select Stellite alloy powder and H13 steel mixed powder as raw materials for preparing the working layer;

[0014] (2) Mixed powder

[0015] The micron-sized Ti alloy powder and the H13 steel alloy powder selected in the above step (1) are uniformly mixed to obtain Ti-containing H13 steel powder, and the Stellite powder and the H13 steel mixed powder selected in the above step (1) are uniformly mixed to obtain Stellite alloy-containing H13 steel powder;

[0016] (3) Laser cladding

[0017] The Ti-containing H13 steel powder and the Stellite alloy-containing H13 steel powder mixed evenly in the above step (2) are respectively subjected to powder baking treatment, and then the Ti-containing H13 steel powder after powder baking treatment is placed in the left powder cylinder of the powder feeder, and the Stellite alloy-containing H13 steel powder after powder baking treatment is placed in the right powder cylinder of the powder feeder; then the left powder cylinder is opened to melt-coat the Ti-containing H13 steel powder on the surface of the nitrided steel as a base layer; after the base layer is melt-coated, the left powder cylinder is closed, and the right powder cylinder is opened to continue to melt-coat the Stellite alloy-containing H13 steel powder on the base layer as a working layer. After the working layer is melt-coated, a composite coating is finally obtained.

[0018] The method for preparing the laser cladding composite coating of the nitriding die steel, wherein: the Ti-containing H13 steel powder in the step (2) is obtained by adding micron-grade Ti powder with an average particle size of 8 to 12 μm and a purity of 99.7% to H13 steel alloy powder with a particle size of 53 to 150 μm in a required mass ratio and mixing them thoroughly.

[0019] The method for preparing the laser cladding composite coating of the nitriding die steel, wherein: in the Ti-containing H13 steel powder in the step (2), the mass ratio of micron-grade Ti powder is 5% to 20%, and the rest is H13 steel powder.

[0020] The method for preparing the laser cladding composite coating of the nitriding die steel, wherein: the H13 steel powder containing Stellite alloy in the step (2) is obtained by adding Stellite alloy powder with a particle size of 50 to 100 μm to H13 steel mixed powder with a particle size of 53 to 150 μm according to the required mass ratio and mixing them thoroughly.

[0021] The method for preparing the laser cladding composite coating of the nitriding die steel comprises the following steps: in the H13 steel powder containing the Stellite alloy, the mass ratio of the Stellite alloy powder is 20% to 50%, and the rest is the H13 steel powder.

[0022] The method for preparing the laser cladding composite coating of the nitriding die steel, wherein: the powder baking treatment of the Ti-containing H13 steel powder in the step (3) is to place the Ti-containing H13 steel powder in a drying oven for drying, the powder baking temperature is 120° C. to 140° C., and the drying time is 2 to 6 hours;

[0023] The powder baking treatment of the H13 steel powder containing the Stellite alloy in the step (3) is to place the H13 steel powder containing the Stellite alloy in a drying oven for drying, the powder baking temperature is 120° C. to 140° C., and the drying time is 2 to 6 hours.

[0024] The method for preparing the laser cladding composite coating of the nitriding die steel, wherein: the preparation methods of the base layer and the working layer in the step (3) are both laser cladding methods;

[0025] The laser cladding process parameters of the base layer are: laser power 1500W, scanning speed 10mm / s, powder feeding rate 10g / min, overlap rate 40%, and scanning mode is unidirectional parallel line filling mode;

[0026] The process parameters of the laser cladding of the working layer are: laser power 1500W, scanning speed 10mm / s, powder feeding rate 10g / min, overlap rate 40%, scanning mode is unidirectional parallel line filling mode, and the laser scanning rotation angle between the base layer and the working layer is 90°.

[0027] The method for preparing the laser cladding composite coating of the nitriding die steel, wherein: the Ti-containing H13 steel powder and the Stellite alloy-containing H13 steel powder are both obtained by mechanical powder mixing.

[0028] The method for preparing the laser cladding composite coating of the nitriding die steel, wherein: the thickness of the composite coating reaches 1.0 mm to 1.5 mm.

[0029] By adopting the above technical solution, the present invention has the following beneficial effects:

[0030] The preparation method of the laser cladding composite coating of the nitriding die steel of the present invention has a reasonable concept and a simple process, and can obtain a composite coating with good interface quality. The composite coating is particularly suitable for steel with a high surface nitrogen content. The present invention adds an appropriate amount of micron-grade Ti powder to the H13 steel powder of the laser cladding base layer, so that the micron-grade Ti and N react in situ, which can effectively reduce the formation of nitrogen pore defects near the cladding interface;

[0031] The present invention designs a wear-resistant and corrosion-resistant coating that meets the service requirements according to the use conditions of the mold steel. The coating is divided into a primer layer and a working layer. The working layer adopts a mixed powder of cobalt-based alloy powder with a particle size of 50-100μm (mass ratio is 20%-50%) and H13 steel powder with a particle size of 53-150μm. The thickness of the composite coating is controlled at 1.0mm-1.5mm based on the elasticity theory and considering the repair cost. Under the premise of taking into account the service conditions and the repair cost, it is beneficial to reduce costs and increase efficiency, and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 It is a flow chart of the method for preparing the laser cladding composite coating of the nitriding die steel of the present invention;

[0034] Figure 2 The SEM images of the Stellite powder, H13 steel powder and Ti powder used in the method for preparing the laser cladding composite coating of the nitriding die steel of the present invention;

[0035] Figure 3 The observation result diagram of the laser cladding of the nitrided H13 steel surface with the Stellite alloy and the H13 steel alloy involved in the preparation method of the laser cladding composite coating of the nitrided die steel of Example 1 of the present invention (wherein Figure 3 In Figure 3 a and Figure 3 b are all surface macroscopic morphologies, Figure 3 c and Figure 3 d are all cross-sectional SEM images);

[0036] Figure 4 The macroscopic morphology and cross-sectional SEM images of the laser cladding layer at different Ti contents involved in the preparation method of the laser cladding composite coating of the nitriding die steel in Example 1 of the present invention ( Figure 4 In Figure 4 a and Figure 4 The Ti content of c is 5%, Figure 4 b and Figure 4 d has a Ti content of 10%);

[0037] Figure 5The macroscopic surface morphology of the working layer under different Stellite contents involved in the method for preparing the laser cladding composite coating of the nitriding die steel in Example 2 of the present invention;

[0038] Figure 6 The SEM image and element scanning result image of the composite coating prepared on the nitrided H13 substrate involved in the preparation method of the laser cladding composite coating of the nitrided die steel in Example 3 of the present invention ( Figure 6 In Figure 6 a is the cross-sectional SEM image, Figure 6 In Figure 6 b is the element line scanning result diagram). DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The present invention is further explained below in conjunction with specific implementation modes.

[0041] like Figure 1-2 As shown, the present embodiment provides a method for preparing a laser cladding composite coating of a nitriding die steel, comprising the following steps:

[0042] (1) Material selection

[0043] The composite coating includes a primer layer and a working layer, and the composite coating has a total of 2 layers. The function of the primer layer is mainly to solve the problem of nitrogen precipitation and release in the molten pool when a high energy density heat source acts on the nitriding matrix; the function of the working layer is mainly to improve the wear resistance and corrosion resistance of the material surface.

[0044] Ti alloy powder and H13 steel alloy powder were selected as raw materials for preparing the base layer. Among them, the absolute value of the Gibbs free energy of TiN is higher than that of TiC. During laser cladding, TiN in the molten pool is easier to form and precipitate than TiC; adding an appropriate amount of micron-sized Ti to the cladding material helps to consume and reduce the nitrogen content of the nitriding layer, so that the probability of nitrogen pores forming at the cladding interface will be greatly reduced. Based on the consideration of interface matching, the base layer is prepared by adding an appropriate amount of Ti alloy powder (i.e., micron-sized Ti powder particles) to the H13 steel alloy powder (the same as the base material). The Ti element reacts with the nitrogen in the nitriding layer in the molten pool, which can effectively reduce the formation of nitrogen pore defects at the interface;

[0045] In order to reduce the crack problem caused by the drastic change of composition and improve the corrosion resistance of the material surface, a cobalt-based alloy powder (i.e., Steelite powder) and H13 steel mixed powder with a mass ratio of 20% to 50% is used as the preparation material for the working layer; wherein, the extremely high cooling rate in the laser molten pool is used to refine the grain size and improve the surface hardness of the working layer. The higher the surface hardness, the smaller the surface contact friction coefficient and the more wear-resistant the surface; at the same time, Steelite alloy has excellent corrosion resistance, and adding a certain proportion of Steelite alloy helps to improve the corrosion resistance of the composite coating surface.

[0046] (2) Mixed powder

[0047] The Ti alloy powder selected in the above step (1) and the H13 steel alloy powder are mixed to obtain Ti-containing H13 steel powder. At the same time, the cobalt-based alloy powder (i.e., Stellite alloy powder) selected in the above step (1) and the H13 steel mixed powder are mixed to obtain Stellite alloy-containing H13 steel powder. Among them, the aforementioned Ti-containing H13 steel powder is obtained by adding micron-grade Ti powder with an average particle size of 8 to 12 μm and a purity of 99.7% to H13 steel alloy powder with a particle size of 53 to 150 μm (the mass ratio of the micron-grade Ti powder is 5% to 20%, and the rest is H13 steel powder), and fully mixing the two by mechanical powder mixing; the aforementioned Stellite alloy-containing H13 steel powder is obtained by adding Stellite alloy powder with a particle size of 50 to 100 μm at a mass ratio of 20% to 50% to H13 steel mixed powder with a particle size of 53 to 150 μm (the proportion of Stellite alloy powder is 20% to 50%, and the rest is H13 steel powder), and fully mixing the two by mechanical powder mixing.

[0048] (3) Laser cladding

[0049] The Ti-containing H13 steel powder and the Stellite alloy-containing H13 steel powder mixed evenly in the above step (2) are placed in a drying oven for baking (the baking temperature is 120°C to 140°C, and the drying time is 2 to 6 hours). Then, the Ti-containing H13 steel powder after baking is placed in the left powder barrel of a high-precision powder feeder. At the same time, the Stellite alloy-containing H13 steel powder after baking is placed in a drying oven for baking. H13 steel powder containing Ti 2 O 2 alloy is placed in the right powder cylinder; after planning the path, the running program is started (that is, after planning the path, the teaching pendant of the multi-axis robot is used to select and run the running program input into the control cabinet, and the robot performs laser cladding according to the input program trajectory and running parameters), the left powder cylinder is opened, and the H13 steel powder containing Ti is clad on the surface of the nitrided steel by the laser cladding method as a base layer; after the base layer cladding is completed, the left powder cylinder is closed, and the right powder cylinder is opened, and the running program is started, and the optimized process parameters are adopted (referring to the key process parameters for controlling the laser cladding process in the file input to the multi-axis robot execution program, such as: laser power, scanning speed, overlap rate, lifting amount, etc., because the thermophysical properties of different alloy powders are quite different, and the combination of the above process parameters is various, there must be an optimization process, so that the forming quality of the laser cladding layer reaches an ideal effect), and the H13 steel powder containing Ti 2 O 2 alloy is continued to be clad on the base layer by the laser cladding method as a working layer. After the working layer cladding is completed, a composite coating is finally obtained. The thickness of the composite coating reaches 1.0 mm to 1.5 mm.

[0050] Based on elasticity theory, when the surface hardness is high and the integrity is good, the location where damage occurs is located hundreds of microns below the surface. Therefore, under the premise of taking into account both service conditions and repair costs, the thickness of the composite coating is designed to be 1.0 mm to 1.5 mm in the present invention, which is conducive to reducing costs and increasing efficiency.

[0051] The present invention is aimed at nitrided steel and is not limited to nitrided H13 steel. Essentially, for steel with a high surface nitrogen content, a coating with good interface quality can be obtained by using the method of the present invention.

[0052] The Ti-containing H13 steel mixed powder is prepared by mechanical powder mixing. In fact, any powder mixing process that can evenly distribute a certain amount of micron-sized Ti powder in the H13 steel powder can achieve the technical effect of the present invention.

[0053] In order to improve the degree of automation, the present invention adopts a program to automatically complete the preparation of the cladding layer (that is, the program file with layered slicing and path planning is output to the multi-axis robot, the program file is selected, and the program file is run using the automatic operation mode on the multi-axis robot teach pendant, and the robot will perform laser cladding according to the established trajectory and parameters). The preparation of the cladding layer can also be completed by manual programming using the teach pendant.

[0054] The present invention is further described below in conjunction with specific embodiments.

[0055] Example 1

[0056] This example is used to illustrate that direct laser cladding of Stellite alloy powder and H13 steel powder on the surface of nitrided steel will produce hole defects at the cladding interface, while adding a certain amount of micron-grade Ti powder to the cladding powder is beneficial to reducing metallurgical defects at the cladding layer interface.

[0057] Using Steelite alloy powder as cladding material, laser cladding experiments were carried out directly on nitrided H13 steel substrates. The laser process parameters used were: laser power 1500W, scanning speed 6mm / s, powder feeding rate 8g / min, overlap rate 35%. Figure 3 As shown in the figure, three repeated experiments were carried out under the same process. It can be seen that the surface flatness of the cladding layer is poor and the surface presents a wavy shape ( Figure 3 a), the cross-sectional microscopic observation results near the molten pool line show that a dark black defect area with a size greater than 200 μm is found on the molten pool line, and nitrogen pores larger than 50 μm are also observed near the molten pool line ( Figure 3 c). Using H13 steel powder as the cladding material, laser cladding experiments were carried out directly on nitrided H13 steel substrates. The laser process parameters used were: laser power of 1500W, powder feeding rate of 10g / min, overlap rate of 40%, scanning speed of 7.5mm / s. The experiment was repeated three times. The surface macroscopic morphology of the prepared cladding layer is shown in Figure 2. Figure 3 As shown in Figure b, it can be seen that the surface of the cladding layer is clearly visible, and visible hole defects are also found on the surface. The microscopic observation results of the cross-section show that there are still dark black defect areas with a size of ~200μm and randomly distributed hole defects near the molten pool line ( Figure 3 d).

[0058] To solve the above problems, a certain amount of micron-sized Ti powder is added to H13 steel powder. Figure 4The macroscopic morphology and cross-sectional SEM images of the laser cladding coatings with Ti additions of 5% and 10% are shown in the figure. The laser process parameters used are: laser power of 1500W, powder feeding rate of 10g / min, overlap rate of 40%, scanning speed of 7.5-10mm / s. Three repeated experiments were conducted. It can be found that when the Ti content is less than 5%, there are obvious pore defects visible to the naked eye on the surface of the cladding layer ( Figure 4 a), with the increase of Ti content, the surface flatness of the cladding layer is better and it has more metallic luster, indicating that the quality of the cladding layer has been improved. The cross-sectional SEM image shows that with the increase of Ti content, the characteristic size and number of defects (dark black area) near the molten pool line also tend to decrease. When the Ti content is 10%, no large hole defects are generated near the molten pool line, and the metallurgical quality of the interface is significantly improved. Based on the above observations, it can be clearly understood that adding a certain amount of micron-sized Ti powder to the cladding powder helps to improve the forming quality of the nitrided steel cladding layer.

[0059] Example 2

[0060] Example 1 shows that for nitrided H13 steel material, adding a certain proportion of micron-grade Ti powder to H13 steel powder helps to improve the forming quality of the cladding layer, and when the Ti powder proportion is 10%, the metallurgical quality of the cladding layer interface can be significantly improved. This Example 2 further shows that although the Ti-containing base layer effectively reduces the metallurgical defects at the interface, if the working layer powder composition ratio is not properly selected, the forming quality of the composite coating will also be reduced.

[0061] A mixed powder of micron-grade Ti and H13 steel containing 10% by mass was used as the cladding material. The base layer was prepared on the nitrided H13 substrate by laser cladding method. The process parameters were: laser power 1500W, scanning speed 10mm / s, powder feeding rate 10g / min, overlap rate 40%, and scanning mode was unidirectional parallel line filling mode. Subsequently, Stellite alloy powder with a mass fraction of 100% was clad on the base layer. The laser process parameters were: laser power 1500W, scanning speed 10mm / s, powder feeding rate 10g / min, overlap rate 40%, and scanning mode was unidirectional parallel line filling mode. The surface macroscopic observation results of the prepared cladding layer are shown in Figure 2. Figure 5 b. A large number of cracks were observed on the surface of the cladding layer, and some cracks ran through the entire width of the cladding layer. When the content of Steelite was reduced to 50%, and 50% of H13 steel powder was added to make a mixed powder, the difference in thermal properties between the working layer and the base layer was reduced without significantly sacrificing the corrosion resistance of the surface layer. The working layer was prepared using the same process parameters. The macroscopic morphology of the cladding layer is shown in Figure 2. Figure 5 As shown in a, no cracks can be observed on the surface.

[0062] Example 3

[0063] In order to fully illustrate the effectiveness of the present invention, firstly, Example 1 illustrates that direct laser cladding on nitrided steel will produce a large number of defects at the interface (i.e., the source of the problem). The present invention innovatively adds micron-grade Ti powder to the H13 steel powder to effectively solve this problem; secondly, Example 2 illustrates the problem of selecting the composition of the working layer powder. Although the corrosion resistance of the surface layer is stronger when the content of Stellite alloy is high, a large number of cracks are prone to appear on the coating surface; finally, a certain amount of micron-grade Ti is added to the base layer to solve the problem of hole defects generated at the cladding interface, and then a certain proportion of H13 powder (the same material as the substrate) is continuously clad on the base layer as the working layer, and a certain amount of Stellite alloy is added to improve the surface corrosion resistance, thereby successfully preparing a composite coating with excellent comprehensive performance.

[0064] Micron-grade Ti powder with a mass fraction of 10% was added to H13 steel alloy powder (particle size 53-150μm) with a particle size of 53-150μm, and the powders were fully mixed by mechanical mixing. The mixed powders were then placed in a drying oven for full drying for 6 hours (the baking temperature was 120°C). The base layer was prepared on the nitrided H13 substrate by laser cladding method. The laser-related process parameters were: laser power 1500W, scanning speed 10mm / s, powder feeding rate 10g / min, overlap rate 40%, and scanning mode was unidirectional parallel line filling mode. At the same time, cobalt-based alloy powder with a mass fraction of 50% and a powder particle size of 50-100μm was added to the H13 steel powder and fully mixed, and then dried in a drying oven for 6h. The working layer was continued to be clad on the base layer by laser cladding method. The laser-related parameters used to prepare the working layer were: laser power 1500W, scanning speed 10mm / s, powder feeding rate 10g / min, overlap rate 40%, scanning mode was unidirectional parallel line filling mode, and the laser scanning rotation angle between the base layer and the working layer was 90°.

[0065] The macroscopic surface morphology of the composite coating prepared on the surface of nitrided H13 steel using the preparation process of the above embodiment is as follows: Figure 5 The cross-sectional SEM and corresponding element analysis results are shown in a. Figure 6 (a, b), the white arrows in the figure indicate the line scanning direction of the element chemical composition change (the scanning position spans the coating surface to the heat affected zone). It can be found that adding 10% micron-grade Ti powder to the base layer can produce a coating with better surface quality ( Figure 5 a), and significantly reduce the probability of nitrogen pore defects near the interface of the substrate cladding layer ( Figure 4 d. Figure 6a), the elements of the base layer and the working layer diffused with each other, the content of elements such as Cr, Co, and Mo gradually decreased, and the content of Fe and Ti gradually increased; between the cladding layer and the heat-affected zone, the content of Ti element showed a slow transition trend, and the elements at the interface diffused to a certain extent. The above results show that the coating and the substrate have formed a good metallurgical bond.

[0066] The invention has reasonable concept and simple process. The composite coating is laser clad on the surface of nitrided steel, and a cladding layer with no obvious holes and crack defects on the interface and excellent performance can be prepared, which is suitable for promotion and application.

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a laser cladding composite coating of a nitriding die steel, characterized in that: Ti powder and H13 steel alloy powder are selected and uniformly mixed to obtain Ti-containing H13 steel powder, wherein the Ti powder is a micron-sized powder; at the same time, Stellite alloy powder and H13 steel mixed powder are selected and uniformly mixed to obtain Stellite alloy-containing H13 steel powder; then the Ti-containing H13 steel powder and the Stellite alloy-containing H13 steel powder are respectively subjected to powder baking treatment; then the Ti-containing H13 steel powder subjected to powder baking treatment is clad on the surface layer of the nitrided steel as a base layer, and the Stellite alloy-containing H13 steel powder is further clad on the base layer as a working layer, so as to finally obtain a composite coating containing a base layer and a working layer; The main steps include: (1) Material selection Select micron-sized Ti powder and H13 steel alloy powder as raw materials for preparing the base layer, and select Stellite alloy powder and H13 steel mixed powder as raw materials for preparing the working layer; (2) Mixed powder The micron-sized Ti powder and H13 steel alloy powder selected in the above step (1) are uniformly mixed to obtain Ti-containing H13 steel powder, and the Stellite powder and H13 steel mixed powder selected in the above step (1) are uniformly mixed to obtain Stellite alloy-containing H13 steel powder; (3) Laser cladding The Ti-containing H13 steel powder and the Stellite alloy-containing H13 steel powder mixed evenly in the above step (2) are respectively subjected to powder baking treatment, and then the Ti-containing H13 steel powder after powder baking treatment is placed in the left powder barrel of the powder feeder, and the Stellite alloy-containing H13 steel powder after powder baking treatment is placed in the right powder barrel of the powder feeder; then the left powder barrel is opened to melt-coat the Ti-containing H13 steel powder on the surface of the nitrided steel as a base layer; after the base layer is melt-coated, the left powder barrel is closed, and the right powder barrel is opened to continue to melt-coat the Stellite alloy-containing H13 steel powder on the base layer as a working layer. After the working layer is melt-coated, a composite coating is finally obtained; The Ti-containing H13 steel powder in step (2) is obtained by adding micron-grade Ti powder with an average particle size of 8 to 12 µm and a purity of 99.7% to H13 steel alloy powder with a particle size of 53 to 150 µm according to a required mass ratio and mixing them thoroughly; In the step (2), in the Ti-containing H13 steel powder, the mass ratio of micron-sized Ti powder is 5% to 20%, and the rest is H13 steel powder; The H13 steel powder containing Stellite alloy in step (2) is obtained by adding Stellite alloy powder with a particle size of 50-100 μm to H13 steel mixed powder with a particle size of 53-150 μm according to a required mass ratio and mixing them thoroughly; In the H13 steel powder containing Stellite alloy, the mass ratio of Stellite alloy powder is 20% to 50%, and the rest is H13 steel powder; The thickness of the composite coating reaches 1.0 mm to 1.5 mm.

2. The method for preparing a laser cladding composite coating of a nitriding die steel according to claim 1, characterized in that: The powder baking treatment of the Ti-containing H13 steel powder in step (3) is to place the Ti-containing H13 steel powder in a drying oven for drying, the powder baking temperature is 120° C. to 140° C., and the drying time is 2 to 6 hours; The powder baking treatment of the H13 steel powder containing Stellite alloy in step (3) is to place the H13 steel powder containing Stellite alloy in a drying oven for drying, the powder baking temperature is 120° C. to 140° C., and the drying time is 2 to 6 hours.

3. The method for preparing the laser cladding composite coating of the nitriding die steel according to claim 1, characterized in that: The preparation method of the base layer and the working layer in step (3) is laser cladding method; The laser cladding process parameters of the base layer are: laser power 1500W, scanning speed 10mm / s, powder feeding rate 10 g / min, overlap rate 40%, and scanning mode is unidirectional parallel line filling mode; The process parameters of the laser cladding of the working layer are: laser power 1500W, scanning speed 10mm / s, powder feeding rate 10g / min, overlap rate 40%, scanning mode is unidirectional parallel line filling mode, and the laser scanning rotation angle between the base layer and the working layer is 90°.

4. The method for preparing a laser cladding composite coating of a nitriding die steel according to claim 1, characterized in that: The Ti-containing H13 steel powder and the Stellite alloy-containing H13 steel powder are both obtained by mechanical powder mixing.